Dentofacial manifestations of fetal warfarin syndrome in a paediatric patient. Issue 1 (17th January 2022) - Rahul, Morankar; Shrivastava, Nikhil; Tewari, Nitesh; Mathur, Vijay
Abstract : Anticoagulant therapy is commonly indicated during pregnancy to prevent thrombosis and prevention of prosthetic heart valve-associated thromboembolic events. Warfarin is a synthetic anticoagulant with low molecular weight and can cross the placenta resulting in congenital abnormalities termed fetal warfarin syndrome. This paper highlights the case of an 8-year-old boy with warfarin embryopathy. It highlights the extraoral and intraoral findings of the case along with the cephalometric analysis and provides insight into the phenotypic variations among the different cases reported in the literature.